2021
DOI: 10.1158/0008-5472.can-20-2511
|View full text |Cite
|
Sign up to set email alerts
|

ELOVL5 Is a Critical and Targetable Fatty Acid Elongase in Prostate Cancer

Abstract: The androgen receptor (AR) is the key oncogenic driver of prostate cancer and despite implementation of novel AR targeting therapies, patient outcomes for metastatic disease remain dismal. There is an urgent need to better understand androgen regulated cellular processes, in order to more effectively target the AR-dependence of prostate cancer cells through new therapeutic vulnerabilities. Transcriptomic studies have consistently identified lipid metabolism as a hallmark of enhanced AR signaling in prostate ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 50 publications
5
59
0
Order By: Relevance
“…Therefore, the observed changes in the relative abundance of PC 34:1 n -7 and PC 34:1 n -9 within prostate tissue ( Figure 2 ) indicate a discrete difference in the ordering of desaturation and elongation reactions, and suggests region-specific aberrations in the SCD-1 and ELOVL5 and/or ELOVL6 enzyme system(s). Indeed, recent work has shown that ELOVL5 is significantly upregulated within prostate cancer and depletion of the elongase lead to the generation of reactive oxidative lipid species and hindered cancer cell growth and proliferation ( 38 ). Previous research has implicated these enzyme systems in cancer, with overexpression of SCD-1 being linked to progression and growth of hepatocellular ( 39 ), renal ( 40 ), colorectal ( 41 ) and prostate ( 42 ) cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the observed changes in the relative abundance of PC 34:1 n -7 and PC 34:1 n -9 within prostate tissue ( Figure 2 ) indicate a discrete difference in the ordering of desaturation and elongation reactions, and suggests region-specific aberrations in the SCD-1 and ELOVL5 and/or ELOVL6 enzyme system(s). Indeed, recent work has shown that ELOVL5 is significantly upregulated within prostate cancer and depletion of the elongase lead to the generation of reactive oxidative lipid species and hindered cancer cell growth and proliferation ( 38 ). Previous research has implicated these enzyme systems in cancer, with overexpression of SCD-1 being linked to progression and growth of hepatocellular ( 39 ), renal ( 40 ), colorectal ( 41 ) and prostate ( 42 ) cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly a possibility is that increased quantities of intracellular fatty acids are beneficial. This is supported by experiments that show that 1) supplementation of fatty acids can rescue growth inhibition due to inhibition of fatty acid synthesis (49,54,56) and 2) inhibition of lipid uptake also inhibits prostate cancer growth (79,80). Indeed the dogma of de novo fatty acid synthesis in cancer is that it is a critical source of lipids that serve as biosynthetic building blocks for cell and organelle membrane formation for rapid proliferation.…”
Section: Benefit Of Fatty Acid Synthesis For Prostate Cancer Progressionmentioning
confidence: 95%
“…Inhibition of the rate-limiting enzyme ACC by RNAi-mediated silencing or by soraphen A reduced proliferation of CRPC cell lines, which could be rescued by addition of palmitate to the media (52,53). Moreover, genetic knock-down of the fatty acid elongases ELOVL5 (54) or ELOVL7 (26) inhibits growth of CRPC xenograft tumors and human tumor explants. Interestingly, ELOVL5 knock-down also reduced metastasis of mouse orthotopic prostate cancer, and in vitro growth could be rescued by supplementation with cis-vaccenic acid, the fatty acid product of ELOVL5 (54).…”
Section: Fatty Acid Synthesis May Drive Prostate Cancer Development and Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…These features were rescued by the supplementation of cis-vaccenic MUFA, a direct product of ELOVL-5 elongation. These data suggest that lipid elongation is a metastasis-promoter metabolic pathway, which is targetable via ELOVL-5 (52). Aside from membrane lipid elongation, ELOVL-5 has more recently been involved in the generation of eicosanoids, inflammatory lipids with potent pro-tumorigenic signaling effects (9).…”
Section: Alterations In Fa Modellingmentioning
confidence: 96%